Rola systemu edukacji w procesach adaptacji migrantów do struktury społecznej. Rozważania na bazie założeń dotyczących alokacyjnej funkcji systemu szkolnego = The role of the education system in the processes of migrants` adaptation to the social structure. Considerations based on the assumptions about the allocation function of the school system - Mikiewicz, Piotr; Sadownik, Alicja; Jurczak-Morris, Marta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses education mechanisms as a tool of individuals` social allocation in the social structure. It presents sociological theories of inequality in education, ascertaining on their basis that the institution of school does not provide equal opportunities to its participants. In particular, migrants? children, on whom the study focuses, are disadvantaged in this matter. Further, the text discusses possible ways of reducing these educational inequalities; three main directions of the integration policy, which should be followed both on the system and the school level, are distinguished and presented.
Keywords: edukacja; migracje; dzieci migrantów; edukacyjne nierówności; education; migrations; migrants` children; inequalities in education